Ectonucleotidase Modulation of Lymphocyte Function in Gut and Liver - Savio, Luiz Eduardo Baggio; Robson, Simon C.; Longhi, Maria Serena (Frontiers in Cell and Developmental Biology, 2021)
Imbalance between regulatory and effector T-lymphocytes contributes to loss of immunotolerance and plays a permissive role in the initiation, perpetuation, and progression of chronic inflammatory diseases and autoimmune disorders. Regulatory/effector cell balance is governed by the CD39 ectonucleotidase, the prototype member of the NTPDase family that hydrolyzes ATP and ADP into AMP, subsequently converted into adenosine by CD73. Generation of adenosine impacts T-cell function as it contributes to the mechanism of suppression of Tregs and confers regulatory properties to pathogenic Th17-cells. CD39 cell distribution, mechanism of regulation and impact on inflammatory and regulatory signaling pathways are also discussed here. Innovative therapeutic strategies to boost CD39 levels and activity by either administering soluble ADPases or interfering with CD39 inhibitory signals are reviewed. Restoration of CD39 levels and function has enormous translational and clinical implications and should be regarded as an additional form of treatment to be deployed in the chronic inflammatory setting. The key role of CD39 in immunoregulation in the context of Crohn’s disease, one of the most frequent manifestations of inflammatory bowel disease, and autoimmune hepatitis, an autoimmune disorder of the liver, is reviewed and discussed here.